Effect of magnesium, micro-nutrients and lime on growth and symbiotic nitrogen fixation in perennial soybean ( Glycine wightii) in a “cerrado” soil - França, Gonçalo E. de; Bahia Filho, Antonio F.C.; Carvalho, Margarida M. de (Pesquisa Agropecuaria Brasileira, 2014)
A greenhouse experiment was carried out with perennial soybeans in a dark-red latosol, using a 25 factorial design, with 3 replications. The objective of this experiment was to study the effect of micro-nutrients, magnesium and lime on growth and symbiotic N2 fixation in perennial soybeans. The following criteria were used to determine the best treatment: dry matter production, total N, nodule weight and % of N, P, K, Ca and Mg in the stems and leaves. Lime had a positive effect on dry matter production with a corresponding increase in total N and % N, P, Ca and Mg. Lime, in the absence of boron, decreased nodule weight. No effect was observe on the variables measured in the study where Mg was added. Boron, in the presence of lime, increased dry matter production, total N and nodule weight. On the other hand, the application of this micronutrient decreased the levels of N, P, K, Ca and Mg in the plant. Zinc also increased dry matter production, total N and nodule weight. Its effect on the % P, % K and % Mg in the plant was negative. Molibdenum in absence of lime increased symbiotic nitrogen fixation by the plant as measured by % and total N.